FTA contributed to the formal recognition of peatlands in Peru - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
FTA research has contributed to Peru’s national Forest Reference Emission Levels (FREL) reported to UNFCCC, a recognition of peatlands in Amazonia and their environmental importance and climate change mitigation potential.